The edge of the fall - Williams, Kate, 1974- (Williams, Kate, 1974- Storms of war trilogy, 2016)
In the aftermath of the Great War, the De Witt family is struggling to piece together the shattered fragments of their lives. Rudolf and his wife Verena, still reeling from the loss of their second son, don't know how to function in the post-war world. Stoneythorpe Hall has become an empty shell with no servants to ensure its upkeep. Celia, the de Witt's youngest daughter, is still desperate to spread her wings and see more of the world. To escape Stoneythorpe and the painful secrets that lie there, she moves to London and embraces life and love in the Roaring Twenties.